2022
DOI: 10.21608/puj.2022.129311.1160
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in identification of potential drug targets and development of novel drugs in parasitic diseases. Part II: Parasite targets

Abstract: Growth and replication (DNA synthesis and gene expression) 1. Nucleic acids synthesisNucleotides serve as monomeric units of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA). They are formed of a nitrogenous base (nucleoside), five-carbon sugars (ribose or deoxyribose), and a phosphate group (1-3 phosphates). Accordingly, they are termed monophosphate (MP), diphosphate (DP), and triphosphate (TP), respectively. Symthesis of DNA and RNA copies requires supply of two nitrogenous bases (purines and pyrimidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…PMM is additionally combined with stearyl amine (SA)-containing phosphatidylcholine (PC) liposomes. PMM-SA-PM revealed enhanced immune protection, antileishmanial activity, and no toxicity …”
Section: Drug Resistance Linked To Mutationmentioning
confidence: 99%
“…PMM is additionally combined with stearyl amine (SA)-containing phosphatidylcholine (PC) liposomes. PMM-SA-PM revealed enhanced immune protection, antileishmanial activity, and no toxicity …”
Section: Drug Resistance Linked To Mutationmentioning
confidence: 99%
“…As previously reviewed [31] , adenosine deaminase (ADA), purine nucleoside phosphorylase (PNP), and HGXPRT are essential enzymes in purine salvage pathway. Besides, inosine monophosphate dehydrogenase (IMPDH) obtained from Staphylococcus aureus, an enzyme producing NADH over time to monitor the activity of purine pathway, gained much attention for treatment of multi-drug resistant bacterial and fungal infections, i.e., a valuable drug target.…”
Section: Drug Targets In Plasmodium Sppmentioning
confidence: 99%
“…Later, virtual screening of 51 inhibitors revealed that MC1742-12 displayed in vitro satisfactory results against P. falciparum, but it failed to reduce parasitemia in P. berghei-infected mice [60] . (iii) BDPs: As previously explained [31] , BDPs are conserved acetyl-lysine-specific protein-interaction modules that play important roles in regulating gene expression and mutations. In other words, they are proteins with a domain known to recognize acetyl-lysine residues on histones.…”
Section: Abazamentioning
confidence: 99%
See 1 more Smart Citation